Intrateam communication and performance in doubles tennis - Lausic, D.; Tennebaum, G.; Eccles, D.; Jeong, A.; Johnson, T. (Research Quarterly for Exercise and Sport, 2009)
Verbal and nonverbal communication is a critical mediator of performance in team sports and yet there is little extant research in sports that involves direct measures of communication. Our study explored communication within NCAA Division I female tennis doubles teams. Video and audio recordings of players during doubles tennis matches captured the communications that took place between and during points. These recordings were coded and sequential analysis computed using the Discussion Analysis Tool software (Jeong, 2003). Results indicated that most communications were emotional (i.e., > 50%) or action statements (i.e., > 25%). Winning teams exhibited significantly different communication sequences than losing teams. In particular, winning teams had a more homogeneous model of communication, which perhaps makes message interpretation more reliable. Finally, winning teams exchanged twice as many messages as losing teams.